THE INFLUENCE OF PROBLEM BASED LEARNING MODEL ANDSOCIAL SKILLS ON LEARNING OUTCOMES OF PKN STUDENTSCLASS IV STATE ELEMENTARY SCHOOL 0308 AEK BARGOT - Leni Sri Ramadhani Siregar; Deny Setiawan; Adi Sutopo (SENSEI RESEARCH CENTER, 2021)
This study aims to analyze: (1) the effect of the Problem Based Learning model is higher than the Direct learning model; (2) Civics learning outcomes of students who have high social skills are higher than students who have low social skills (3) the interaction between Problem Based Learning learning models and social skills in influencing Civics learning outcomes of fourth grade students. The research is in the form of a Quasi Experimental Design with a 2x2 factorial. The instruments used are Civics learning outcomes tests and Social Skills instruments. Data analysis usingtwo-way anova. The results of the research show: (1) There is an effect of the Problem Based Learning learning model on the Civics learning outcomes of students in grade IV SD Negeri 0308 Aek Bargot; (2) Civics learning outcomes of students who have high social skills are higher than students who have low social skills; (3) There is an interaction between the Problem Based Learning model and social skills on student learning outcomes of Civics at SD Negeri 0308 Aek Bargot.